Determination of nanoparticle localisation within subcellular organelles in vitro using Raman spectroscopy. Issue 23 (4th November 2015) - Efeoglu, Esen; Keating, Mark; McIntyre, Jennifer; Casey, Alan; Byrne, Hugh J.
Abstract : Raman spectroscopy with the aid of Multivariate Analysis techniques is a powerful analytical tool to determine the localisation of nanoparticles and their local environment within subcellular organelles. Abstract : Ease of sample preparation, narrow spectral bandwidth and minimal influence from water are features of Raman spectroscopy which make it a powerful, label-free way to study a wide range of biological structures and phenomena. In this context, given the concerns over their toxicology arising from their increased production and use, evaluation of nanoparticle uptake and localisation in biological systems and determination of the mechanisms of subcellular interaction and trafficking can provide long-term solutions for nanotoxicology, and potential strategies for nanomedicine. In this study, Raman spectroscopy is explored to monitor the sequential trafficking of nanoparticles through subcellular organelles in vitro and to establish the spectroscopic signatures of those organelles. A549 human lung carcinoma cells were exposed to 40 nm carboxylate-modified and fluorescently-labelled polystyrene nanoparticles for 4, 12 and 24 h. Raman spectroscopy was applied to nanoparticle exposed cells to determine the localisation within cellular compartments. Confocal laser scanning fluorescence microscopy (CLSM) with different organelle staining kits confirmed the localisation of the nanoparticles in organelles at the chosen exposure periods and co-localization was quantified using ImageJ with the JACoP colocalisation plugin. To confirm nanoparticle localisation and elucidate the spectroscopic signatures of the different subcellular organelles, a combination of K -means clustering (KMCA) and principal components analysis (PCA) was applied to the Raman spectroscopic maps. The study showed the applicability of the techniques for elucidation of the localisation of polystyrene nanoparticles within the cell as well as determination of their local environment, differentiating the spectral signatures of intracellular compartments such as endosomes, lysosomes and endoplasmic reticulum, in a completely label free manner.